The effect of innovation on income : an empirical analysis for the regions of Türkiye - Şahin, Pelin (My University, 2025)
Bu tez, 2010-2021 yılları arasında inovasyonun kişi başına düşen gelir üzerindeki etkisini Türkiye’nin bölgeleri bağlamında incelemektedir. Bölgesel analizde inovasyon üç farklı değişken kullanarak ölçülmüştür; kişi başı Ar-Ge yatırımları, toplam nüfusa göre Ar-Ge çalışanlarının payı ve kişi başına tescilli patentler. Ampirik analiz, sabit etkiler (FE) panel tahmini ve iki aşamalı Genelleştirilmiş Momentler Metodu (GMM) olmak üzere iki farklı metodolojiyi içermektedir. Statik ve dinamik analizler sırasıyla NUTS1 ve NUTS2 düzeyindeki bölgeler için yürütülmüştür. Sonuçlar inovasyon göstergesi olarak kullanılan değişkenlerle kişi başı gelir arasında pozitif ve anlamlı bir ilişki olduğunu göstermektedir. İki aşamalı GMM sonuçları ilişkinin U şeklinde olduğunu vurgulamaktadır, etki belirli bir eşikten sonra pozitif hale gelmektedir. Ek olarak, sigma yakınsaması ve kulüp yakınsaması metodolojileri kullanılarak NUTS3 düzeyindeki inovasyon yakınsaması araştırılmıştır. Varyasyon katsayısı (CV), Batı ve Doğu illerde ya da Türkiye genelinde sigma yakınsaması vurgulamamaktadır. Log t regresyon sonucu da 81 ilde mutlak yakınsama olmadığını göstermektedir. Bölgeler, farklı durağan durum değerine sahip üç farklı inovasyon kulübü oluşturmaktadır.

This thesis conducts a detailed regional analysis for innovations’ impact on income level for Türkiye between the period 2010-2021. Innovative activity is measured with various proxies of innovation inputs (R&D investment, R&D personnel) and innovation output (patents) within different models. Fixed-effect (FE) and Generalized Method of Moments (GMM) methodologies are employed for empirical investigation. Static and dynamic analyses are conducted for NUTS1 and NUTS2 regions, respectively. Accordingly, innovativeness has a positive impact on per capita income within Türkiye’s regions. System GMM results reveal that impact follows a U-shaped pattern, that is positive correlation exists between innovation and per capita income after initial period of negative relationship. Furthermore, innovation convergence among NUTS3 regions is investigated with sigma convergence and club convergence methodologies. Coefficient of variation (i.e. sigma convergence) does not demonstrate tendency towards convergence in Western regions, Eastern regions, or Türkiye. Additionally, log t regression does not indicate absolute convergence in 81 provinces. Rather, regions form three innovation clubs, which consist of 6, 73, and 2 provinces, that converge to their respective steady-states.
İnovasyonun gelir üzerindeki etkisi : Türkiye bölgeleri için ampirik bir analiz
Keywords: Bölgesel Analiz; Economics; Ekonomi; Gelir dağılımı; Genelleştirilmiş Momentler Metodu; Generalized Method of Moments; Income distribution; Innovation; İnovasyon Club Convergence; Kulüp Yakınsaması; Regional Analysis; Turkey; Türkiye